Implikasi Program Kampung Iklim (ProKlim) terhadap Pemberdayaan Ekonomi Masyarakat di Desa Gondangmanis Kabupaten Kudus (Jurnal Ekonomi dan Bisnis Islam, 2025)
AbstractThe Climate Village Program (ProKlim) is an effort to strengthen community-based climate resilience through climate change adaptation and mitigation actions. This research aims to analyze the implications of ProKlim on community economic empowerment in Gondangmanis Village, Kudus Regency, with a focus on strengthening the local economy in depth and sustainably. The method used is field research with a descriptive qualitative approach, through observation, interviews, and documentation. Data analysis was carried out through the stages of data collection, reduction, presentation, and conclusion. The results showed that the implementation of ProKlim had a positive impact on community economic empowerment. The success of the program is supported by collaboration between parties and contributions through increased income and sustainability of the village economy, such as strengthening food security from yard land and waste management. These efforts reduce market dependence and reduce household expenses. Assistance and training from the government and related parties also increase the economic capacity of the community. However, community participation is still limited, posing a challenge in optimizing the program. Therefore, continuous education is needed to get the community more actively involved. Strengthening village government support is needed through regulations, budgets, and market access. Related agencies are advised to provide intensive assistance, including routine training and monitoring. In addition, a long-term evaluation of the economic impact of ProKlim is needed to ensure the sustainability of the program's benefits in improving community welfare.Keywords: Climate Village Program (ProKlim); Community Economic Empowerment. AbstrakProgram Kampung Iklim (ProKlim) merupakan upaya penguatan ketahanan iklim berbasis komunitas melalui aksi adaptasi dan mitigasi perubahan iklim. Penelitian ini bertujuan menganalisis implikasi ProKlim terhadap pemberdayaan ekonomi masyarakat di Desa Gondangmanis, Kabupaten Kudus, dengan fokus pada penguatan ekonomi lokal yang mendalam dan berkelanjutan. Metode yang digunakan adalah penelitian lapangan dengan pendekatan kualitatif deskriptif, melalui observasi, wawancara, dan dokumentasi. Analisis data dilakukan melalui tahapan pengumpulan, reduksi, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi ProKlim memberikan dampak positif terhadap pemberdayaan ekonomi masyarakat. Keberhasilan program didukung kolaborasi antar pihak serta kontribusi melalui peningkatan pendapatan dan keberlanjutan ekonomi desa, seperti penguatan ketahanan pangan dari lahan pekarangan dan pengelolaan sampah. Upaya ini mengurangi ketergantungan pasar dan menekan pengeluaran rumah tangga. Pendampingan dan pelatihan dari pemerintah dan pihak terkait juga meningkatkan kapasitas ekonomi masyarakat. Namun, partisipasi masyarakat masih terbatas, menjadi tantangan dalam optimalisasi program. Oleh karena itu, edukasi berkelanjutan agar masyarakat lebih aktif terlibat. Penguatan dukungan pemerintah desa diperlukan melalui regulasi, anggaran, dan akses pasar. Dinas terkait disarankan memberikan pendampingan intensif, termasuk pelatihan dan monitoring rutin. Selain itu, diperlukan evaluasi jangka panjang terhadap dampak ekonomi ProKlim untuk memastikan keberlanjutan manfaat program dalam meningkatkan kesejahteraan masyarakat.Kata Kunci: Program Kampung Iklim (ProKlim); Pemberdayaan Ekonomi Masyarakat.